Propofol Induces Cardioprotection Against Ischemia-Reperfusion Injury via Suppression of Transient Receptor Potential Vanilloid 4 Channel - Wang, Binbin; Wu, Qiongfeng; Liao, Jie; Zhang, Shaoshao; Liu, Huixia; Yang, Cui; Dong, Qian; Zhao, Ning; Huang, Zhengrong; Guo, Kefang; Du, Yimei (Frontiers in Pharmacology, 2019)
Ca2+ entry via the transient receptor potential vanilloid 4 (TRPV4) channel contributes to Ca2+ overload and triggers many pathophysiological conditions, including myocardial ischemia/reperfusion (I/R) injury. Propofol, a widely used intravenous anaesthetic, attenuates myocardial I/R injury. However, the mechanism of propofol remains to be examined. The present study aims to test the hypothesis that propofol attenuates myocardial I/R injury through the suppression of TRPV4. We used a murine ex vivo model of myocardial I/R and in vitro cultured myocytes subjected to hypoxia/reoxygenation (H/R). Propofol or TRPV4 antagonist HC-067047 attenuates myocardial I/R injury in isolated hearts. In addition, propofol, HC-067047, or TRPV4-siRNA attenuates H/R-induced intracellular Ca2+ concentration ([Ca2+]i) increase and cell viability reduction. On the contrary, TRPV4 agonist GSK1016790A exacerbates both ex vivo and in vitro myocardial injury. Pretreatment with propofol reverses the myocardial injury and intracellular Ca2+ overload induced by GSK1016790A at least in vitro. However, neither the combination of propofol and HC-067047 nor applying propofol to cells transfected with TRPV4-siRNA creates additional protective effects. In addition, propofol dose-dependently inhibits TRPV4-mediated Ca2+ entry induced by GSK1016790A and 4α-PDD. Propofol attenuates myocardial I/R injury partially through the suppression of TRPV4 channel and the subsequent inhibition of intracellular Ca2+ overload.